2023
DOI: 10.1007/s10518-023-01673-3
|View full text |Cite
|
Sign up to set email alerts
|

Rubber-soil mixtures: use of grading entropy theory to evaluate stiffness and liquefaction susceptibility

Abstract: Rubber-soil mixtures are known to have mechanical properties that enable their use in backfills, road construction or geotechnical seismic isolation systems. The complexity of these mixtures comes from adding soft (i.e. rubber) particles that increases the number of particle properties to consider when studying the macroscopic behaviour. The distinction between sand-like and rubber-like behaviour is normally presented in relation to the rubber content and size ratio between particles. It is however unknown how… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…The different mixing ratios of sand and tire chips were selected in order to cover a wide range of tire ratios, in order to better see the different behaviors with the variation in tire content, sand-like and rubber-like (Kim & Santamarina 2008;Senetakis & Anastasiadis 2015). It has to be noted that most of the studies in literature are focusing on tire ratios up to 40% (Promputthangkoon and Hyde 2007;Mashiri et al 2016;Bernal-Sanchez 2020). Also, Hyodo et al (2008), has shown that the addition of tires can be effective against liquefaction above 30% tire content.…”
Section: Triaxial Testing Programmementioning
confidence: 99%
See 2 more Smart Citations
“…The different mixing ratios of sand and tire chips were selected in order to cover a wide range of tire ratios, in order to better see the different behaviors with the variation in tire content, sand-like and rubber-like (Kim & Santamarina 2008;Senetakis & Anastasiadis 2015). It has to be noted that most of the studies in literature are focusing on tire ratios up to 40% (Promputthangkoon and Hyde 2007;Mashiri et al 2016;Bernal-Sanchez 2020). Also, Hyodo et al (2008), has shown that the addition of tires can be effective against liquefaction above 30% tire content.…”
Section: Triaxial Testing Programmementioning
confidence: 99%
“…Previous research on the monotonic behaviour of sandtire mixtures, has proved that the size and shape characteristics of the tire chips used in the mixture can have a major impact on its shear strength. A distinction of scrap tire chips into different sizes and shapes can be found in Bernal-Sanchez (2020), based on ASTM D6270. Numerous studies have demonstrated that when the waste tires are added in the sand as tire derived aggregate (tire chips or shreds), the overall shear strength of the mixture can increase for up to certain tire ratio, which in most cases is below 30% (Edil and Bosscher 1994;Foose et al 1996;Tatlisoz et al 1998;Wu et al 2002;Zornberg et al 2004;Ghazavi and Sakhi 2005;Attom 2006;Rao and Dutta 2006;Kim and Santamarina 2008;Edincliler et al 2010;Cabalar 2011;Mohamad et al 2013;Balunaini et al 2014;Fu et al 2014;Mashiri et al 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dynamic soil-foundation-structure interaction and its favourable effects can be facilitated in a controlled manner by modifying the foundation soils to lengthen the natural period of the system and dissipate seismic wave energy without causing undesirable permanent ground deformations. Half of the articles in this special issue focus on GSI systems that are based on this mechanism (Aloisio et al 2022;Bernal-Sanchez et al 2023;Chiaro et al 2022;Dhanya et al 2023;Edinçliler and Yildiz 2023;Tsang 2022;Vratsikidis and Pitilakis 2022). 2.…”
mentioning
confidence: 99%
“…A wide range of materials have been explored for creating GSI systems. Amongst these, rubber-soil mixtures have been the most researched materials (Bernal-Sanchez et al 2023;Chiaro et al 2022;Dhanya et al 2023; Forcellini and Alzabeebee 2022; Nikitas and Bhattacharya 2023; Vratsikidis and Pitilakis 2022), whilst there is a case study with the use of whole waste tyres (Hazarika et al 2023). Meanwhile, other materials have also been investigated, including EPS beads (Edinçliler and Yildiz 2023), geosynthetics (Banović et al 2022;Dhanya et al 2023), stone pebbles (Banović et al 2022), sand, timber and PVC (Tsiavos et al 2022), polyurethane (Gatto et al 2022), super absorbent polymers (SAP) (Somma and Flora 2023), as well as various high-damping (Aloisio et al 2022) and low-modulus materials (Tsang 2022).…”
mentioning
confidence: 99%